Pengaruh Pengeluaran Pemerintah Bidang Kesehatan terhadap Pertumbuhan Ekonomi: studi kasus 508 kabupaten/kota di Indonesia - Trianto, Dian; Sihaloho, Estro Dariatno (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2023)
People's lives are impacted by their health, which must be preserved. A nation's economy frequently undervalues the health sector. This study aims to see the effect that government spending on health has on economic growth in 508 regions in Indonesia from 2017 to 2019. The method used in this study is panel data regression analysis with the Fixed effect model (FEM) approach. The data used in this study are secondary data obtained from the Central Statistics Agency (BPS) and the Ministry of Finance of the Republic of Indonesia. The study's findings show that while government expenditure on health and education has a positive and significant impact on economic growth, the rate of population expansion has a negative and significant impact.